An Efficient Integrity Verification based Multi-User Cloud Access Control Framework using Block Chain Technology on EHR Database - Sravanthi, Keesara; Sekhar, P Chandra (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Most of the traditional block chain based medical applications are insecure and difficult to provide strong data integrity with variable size due to large number of transactions and data storage type. Conventional healthcare software often faces security risks due to their reliance on fixed variables. On the other hand, cloud storage solutions designed for medical use provide improved data protection and computational security through the use of blockchain-based data structures and advanced memory management. The challenge of ensuring data security intensifies as media files grow larger on both public and private cloud services. This complexity is further amplified by the variety of file formats and the multi-dimensional nature of the data. To address these challenges, a novel mathematical chaotic function based multi-client encryption and decryption model is proposed in order to improve traditional block-chain frameworks on large cloud electronic health record(HER) datasets. In this work, a hybrid dynamic-sized hash verification and encryption framework in a cloud environment to provide data security for large medical databases. The approach enhances security in a real-time cloud computing environment. Experimental results indicate that it outperforms traditional blockchain frameworks for medical data types.